Testosterone replacement therapy in men with type 2 diabetes mellitus and functional hypogonadism –an Integrated Diabetes and Endocrine Academy (IDEA) consensus guideline. Issue 4 (July 2021) - Majumdar, Sujoy; Mukherjee, Jagat Jyoti; Ray, Subir; Goswami, Soumik; Jude, Edward; Biswas, Ajoy; Hanumanthu, Ajay; John, Mathew; Sinha, Binayak; Ghoshal, Samit; Kota, Sunil; Sharma, Surendra Kumar; et al.
Abstract: Background: Though testosterone replacement therapy in men with organic hypogonadism is established, its role in men with type 2 diabetes mellitus (T2DM) and functional hypogonadism is unclear. Methods: Thirteen experts addressed ten topic-specific questions after an in-depth review of literature, where all relevant issues were critically evaluated. Results: Ten recommendations concerning diagnosis and management of men with T2DM and functional hypogonadism have been put forward. Conclusion: Routine measurement of serum testosterone in all, and inappropriate replacement of testosterone in asymptomatic T2DM men with functional hypogonadism and borderline low serum testosterone values, is not recommended. Highlights: Functional hypogonadism in men with type 2 diabetes mellitus is a result of complex interactions between multiple factors. Measure serum testosterone in men with T2DM only when they exhibit one or more core symptoms of low serum testosterone. Do not measure serum testosterone routinely in all asymptomatic men with T2DM or in those with non-specific symptoms. Offer testosterone therapy to men with T2DM with core symptoms when total testosterone value is < 2.3 ng/ml (8 nmol/L).